Effectiveness of Music Therapy in Reducing Depressive Symptoms in Young Adult Patients: A Randomized Controlled Trial - Salsabila Azzahra Putri (Acta Psychologia, 2024)
This study investigates the effectiveness of music therapy in reducing depressive symptoms among young adult patients. A randomized controlled trial (RCT) design was employed, with participants aged 18 to 25 randomly assigned to either a music therapy intervention group or a control group receiving standard care. Depressive symptoms were assessed using standardized measures such as the Beck Depression Inventory (BDI-II) or the Patient Health Questionnaire-9 (PHQ-9) at baseline, post-intervention, and follow-up assessments. Results revealed significant reductions in depressive symptom severity in the music therapy group compared to the control group, with effect sizes ranging from moderate to large. Subgroup analyses indicated consistent treatment effects across demographic and clinical subgroups, suggesting the robustness and generalizability of the intervention. Findings underscore the therapeutic potential of music therapy in addressing depression among young adults and highlight the importance of integrating music therapy into comprehensive mental health care approaches.